“HE WAS THE SON OF A RURAL MAN AND BECAME THE LORD IN THE KINGDOM OF SPIRIT”: TARAS SHEVCHENKO’S CREATIVE WORKS IN IVAN FRANKO’S LITERARY-CRITICAL RECEPTION - Holod, R. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In this article the hereditary connection between Taras Shevchenko and Ivan Franko creative work is studied in the Ukrainian literary tradition discourse. Through the prism of Franko’s literary and critical reception of T. Shevchenko’s creative work the causes of coincidences and differences in the idea and aesthetic conceptions of both authors are determined.